Design of an in-canopy sprinkler monitoring system for center pivot irrigation - Akin, Aaron Alexander (Kansas State University, 2018)
Recent innovations in the irrigation industry indicate a transition to more water efficient and uniform systems. This transition is necessary to preserve limited aquifer resources used by irrigation systems in the U.S. Great Plains where center pivot irrigation has become the dominant irrigation method. New in-canopy sprinkler packages have allowed these center pivot systems to operate more efficiently and uniformly, however, these in-canopy sprinklers hang low in the canopy and have the potential to become entangled in crop biomass and detach from the center pivot. Detached in-canopy sprinklers can impact the uniformity of the irrigation system resulting in decreased crop yields by disrupting the designed flow and pressure requirements of the sprinkler package. Therefore, it is crucial that producers detect and replace missing in-canopy sprinklers immediately. The current method to detect missing in-canopy sprinklers is manual inspection along the center pivot which uses significant time and labor. A monitoring system to alert the user of any detachments can eliminate unnecessary exploration and direct the user to the specific location of the detached in-canopy sprinkler. A prototype in-canopy sprinkler monitoring system was designed to monitor in-canopy sprinklers on a center pivot irrigation system and alerts the user when and where an in-canopy sprinkler becomes detached from the center pivot span. The system utilizes three major components to accomplish this task: a master controller node, a series of sprinkler nodes, and a digital compass node. The master controller node requests the status of in-canopy sprinklers from each connected sprinkler node, which constantly monitors its connected in-canopy sprinkler, and if a sprinkler is found to be missing alerts the user via an SMS text message sent to their cell phone that the in-canopy sprinkler is missing and can be found at specific geographic coordinates. The master controller node calculates the geographic coordinates of the detached in-canopy sprinkler by requesting the current compass bearing angle of the center pivot span from the digital compass node. This angle, combined with the known coordinates of the pivot point of the center pivot system and radius of the detached in-canopy sprinkler from the pivot point can be used to calculate the coordinates of the detached in-canopy sprinkler. To test the performance of the designed system, it was connected to a demonstration center pivot and several trials were performed. The demonstration center pivot consisted of a rotatable span with eight detachable drop hoses and in-canopy sprinklers. Trials performed were designed to test the system’s ability to react to detached in-canopy sprinklers and drop hoses, detect and identify issues that might arise during normal operation, and respond to user’s SMS text messages with the proper system information as part of the user interface. The system successfully passed each set of trials ensuring that this prototype will accurately detect when and where an in-canopy sprinkler becomes detached and promptly alert the user.
Keywords: In-canopy sprinkler; Center pivot; Irrigation; Monitoring system